Pelvic floor muscle training for overactive bladder symptoms – A prospective study - Fitz,Fátima (2017)
Summary Introduction: Pelvic floor muscle training (PFMT) involves the contraction of the puborectal, anal sphincter and external urethral muscles, inhibiting the detrusor contraction, what justify its use in the treatment of overactive bladder (OAB) symptoms. Objective: To verify the effects of isolated PFMT on the symptoms of OAB. Method: Prospective clinical trial with 27 women with mixed urinary incontinence (MUI), with predominance of OAB symptoms and loss ≥ 2 g in the pad test. It was evaluated: pelvic floor muscles (PFMs) function (digital palpation and manometry); urinary symptoms (nocturia, frequency and urinary loss); degree of discomfort of OAB symptoms; and quality of life (Incontinence Quality-of-Life Questionnaire [I-QoL]). The PFMT program consisted of 24 outpatient sessions (2x/week + home PFMT). The Mann-Whitney and Wilcoxon tests (with a significance level of 5%) were used to analyse the data. Results: There was a significant improvement of the urinary symptoms to the pad test (5.8±9.7, p<0.001), urinary loss (0.7±1.1, p=0.005) and nocturia (0.8±0.9, p=0.011). Reduction in the degree of discomfort of urinary symptoms was observed according to OAB-V8 questionnaire (10.0±7.7, p=0.001). There were also significant results in PFMs function: Oxford (3.6±0.9, p=0.001), endurance (5.2±1.8, p<0.001), fast (8.9±1.5, p<0.001) and manometry (26.6±15.8, p=0.003). In addition, quality of life had a significant improvement in the three domains evaluated by I-QoL. Conclusion: The PFMT without any additional guidelines improves the symptomatology, the function of PFMs and the quality of life of women with OAB symptoms.